Simulador didático de estimação fasorial e localização de faltas em linhas de transmissão trifásicas (self3∅) - Nascimento, Cleydson Adller de Castro (Universidade Federal Rural do Semi-Árido, 2020)
A transmission line or equipment in the electrical system that is more conducive to an electrical failure and, due to its large extension, is usually located in regions far from urban centers and with impaired mobility. Based on these conditions, the use of fault location techniques appears as a solution to identify with precision and speed the point of fault. Most location algorithms employ phasors measured at the transmission line terminals, so that, to obtain these phasors, methods of phasor estimation are needed. The objective of this work is to develop the Didactic Simulator for Phasor Estimation and Fault Location in Three-Phase Transmission Lines (SELF3∅) in order to apply the performance of phasor estimation algoritms, as well as different fault techniques location, in order to become a tool to support the teaching of electrical engineering courses. In addition to the interactive platform, this simulator can be used in the teaching-learning process in electrical engineering courses, it also offers a fast and concise form of graphical and numerical solutions aimed at fasor estimation and fault technique location, it can also be used in academic research. To validade the didactic simulator, compare your results with the ATP software in five scenarios, for a topology using measurements with two or three terminals
Keywords: Estimação fasorial; Localização de faltas; Simulador didático; Interface gráfica; Phasor estimation; Fault location technique; Didactic simulator; User interface; ENGENHARIAS::ENGENHARIA ELETRICA